2018
DOI: 10.1007/s00217-018-3059-7
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Fusarium-infected and healthy wheat kernels based on features from hyperspectral images and flatbed scanner images: a comparative analysis

Abstract: Wheat infections caused by fungi of the genus Fusarium decrease yields and have serious economic consequences. The produced mycotoxins have harmful effects on human and animal health. The aim of this study was to develop classification models based on selected textural parameters to distinguish between infected and healthy wheat kernels. The classification accuracy of kernels positioned on the ventral side was determined at 78-100% in the model based on textural parameters from hyperspectral images, and at 95-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 29 publications
(40 reference statements)
1
28
0
Order By: Relevance
“…The classification accuracies noted in this study are similar to those reported by Ropelewska and Zapotoczny (2018) in the classification of infected and healthy wheat kernels. In models containing textural features from the ventral and dorsal sides of kernels, Ropelewska and Zapotoczny (2018) observed classification accuracies in the range of 94-100% for images acquired with a flatbed scanner and 76-98% for hyperspectral images. Jirsa and Polišenska (2011) reported 85% accuracy in infected and healthy wheat kernels classified with the use of a model containing color descriptors.…”
Section: Selected Attributes Rgb Rs4rzglevnonusupporting
confidence: 89%
“…The classification accuracies noted in this study are similar to those reported by Ropelewska and Zapotoczny (2018) in the classification of infected and healthy wheat kernels. In models containing textural features from the ventral and dorsal sides of kernels, Ropelewska and Zapotoczny (2018) observed classification accuracies in the range of 94-100% for images acquired with a flatbed scanner and 76-98% for hyperspectral images. Jirsa and Polišenska (2011) reported 85% accuracy in infected and healthy wheat kernels classified with the use of a model containing color descriptors.…”
Section: Selected Attributes Rgb Rs4rzglevnonusupporting
confidence: 89%
“…The scab identification model constructed by support vector machine (SVM) and back propagation neural network achieved excellent results and an accuracy of more than 90%. Ewa et al [8] constructed a classification model based on texture parameters of hyperspectral images to identify infected kernels, and ventral kernels were classified with 100% accuracy. These studies all achieved good results, and they all directly identified the infected or uninfected kernels through hyperspectral technology in the laboratory.…”
Section: Introduction mentioning
confidence: 99%
“…DON, commonly known as vomitoxin, has acute adverse effects in animals, including food refusal, diarrhea, emesis, alimentary hemorrhaging, and contact dermatitis [4,5]. FHB of wheat not only causes a significant drop in food production, but the DON produced by pathogens also hurts human and animal health, causing food safety problems [6,7]. Therefore, it is important to monitor the health condition of wheat in the field pre-harvest, and to identify the diseased ears.FHB is caused by fungal infection, which affects the normal physiological function of wheat and changes the external morphology and internal physiological structure [8][9][10].…”
mentioning
confidence: 99%
“…The constructed linear discriminant analysis SVM and back propagation (BP) neural network models have good success in identifying FHB-infected kernels, with accuracy rates above 90% [13]. Ewa et al (2018) constructed a classification model based on texture parameters of hyperspectral images to identify the infected kernels, and kernels positioned on the ventral side were classified with 100% accuracy [6]. Delwiche et al (2019) used hyperspectral imaging on individual kernels and linear discriminant analysis models to differentiate between healthy and Fusarium-damaged kernels based on the mean reflectance values of the interior pixels of each kernel at four wavelengths (1100, 1197, 1308, and 1394 nm).…”
mentioning
confidence: 99%